IMMIGRANT YOUTH IN CANADIAN HEALTH PROMOTING SCHOOLS: A LITERATURE REVIEW - Nyika, Lawrence; McPherson, Charmaine; Murray-Orr, Anne (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2017)
In this essay, we review empirical, theoretical, and substantial grey literature in relation to immigrant youth and health promoting schools (HPS). We examine the health promotion concept to consider how it may inform the HPS model. Using Canada as an example, we examine current immigrant youth demographics and define several key terms including immigrant, youth, and health. Our review highlights important knowledge gaps related to the role of education and migration as antecedents to immigrant youth health and wellbeing as well as qualitative and educational research approaches. We conclude by providing recommendations for future immigrant youth research in the context of HPS.